Evaluation of scaffold microstructure and comparison of cell seeding methods using micro-computed tomography-based tools. Issue 165 (29th April 2020) - Palmroth, Aleksi; Pitkänen, Sanna; Hannula, Markus; Paakinaho, Kaarlo; Hyttinen, Jari; Miettinen, Susanna; Kellomäki, Minna
Abstract : Micro-computed tomography (micro-CT) provides a means to analyse and model three-dimensional (3D) tissue engineering scaffolds. This study proposes a set of micro-CT-based tools firstly for evaluating the microstructure of scaffolds and secondly for comparing different cell seeding methods. The pore size, porosity and pore interconnectivity of supercritical CO2 processed poly(l -lactide-co- ɛ -caprolactone) (PLCL) and PLCL/β-tricalcium phosphate scaffolds were analysed using computational micro-CT models. The models were supplemented with an experimental method, where iron-labelled microspheres were seeded into the scaffolds and micro-CT imaged to assess their infiltration into the scaffolds. After examining the scaffold architecture, human adipose-derived stem cells (hASCs) were seeded into the scaffolds using five different cell seeding methods. Cell viability, number and 3D distribution were evaluated. The distribution of the cells was analysed using micro-CT by labelling the hASCs with ultrasmall paramagnetic iron oxide nanoparticles. Among the tested seeding methods, a forced fluid flow-based technique resulted in an enhanced cell infiltration throughout the scaffolds compared with static seeding. The current study provides an excellent set of tools for the development of scaffolds and for the design of 3D cell culture experiments.